FREEDOM OR CONSTRAINT: THE SPEEDING BICYCLE AND THE INDUSTRIAL SUBJECT IN H. G. WELLS'S THE WHEELS OF CHANCE. Issue 2 (5th May 2017) - Chen, Eva
Abstract : In this passage, quoted from Grant Allen's 1897 bestseller The Type-writer Girl, the New-Woman-turned-typist Juliet Appleton decides to quit typing in a London law office where she is forced to "click, click, click all day like a machine." As an alternative and a release, she jumps on her bicycle and rides for an "idyllic" anarchic farm in the countryside (11). There across the Weald of Sussex and Surrey, the bicycling Juliet encounters two other forms of mobility, that of the train and the horse-driven carriage. The train, an icon of industrial modernity that "annihilated time and space" (Schivelbusch 36), rumbles brutally over the green fields and terrifies the horses, which are symbols of a natural, organic, preindustrial world. But Juliet's bicycle seems to create a balance between the two worlds. The bicycle as the never-failing steel horse enables her to utilize the achievements of industrial mechanization and also allows for a degree of freedom and human agency. Juliet is portrayed as a true modern heroine and an "unabashed" daughter of the industrial age, because she seems to possess a new subjectivity bred and made possible by the partnership between machine and nature, mechanical power and organic energy.